Influences of Mg Doping on the Electrochemical Performance of TiO2 Nanodots Based Biosensor Electrodes - M. S. H. Al-Furjan; Kui Cheng; Wenjian Weng (Advances in Materials Science and Engineering)
Electrochemical biosensors are essential for health monitors to help in diagnosis and detection of diseases. Enzyme adsorptions on biosensor electrodes and direct electron transfer between them have been recognized as key factors to affect biosensor performance. TiO2 has a good protein adsorption ability and facilitates having more enzyme adsorption and better electron transfer. In this work, Mg ions are introduced into TiO2 nanodots in order to further improve electrode performance because Mg ions are considered to have good affinity with proteins or enzymes. Mg doped TiO2 nanodots on Ti substrates were prepared by spin-coating and calcining. The effects of Mg doping on the nanodots morphology and performance of the electrodes were investigated. The density and size of TiO2 nanodots were obviously changed with Mg doping. The sensitivity of 2% Mg doped TiO2 nanodots based biosensor electrode increased to 1377.64 from 897.8 µA mM−1 cm−2 and its KMapp decreases to 0.83 from 1.27 mM, implying that the enzyme achieves higher catalytic efficiency due to better affinity of the enzyme with the Mg doped TiO2. The present work could provide an alternative to improve biosensor performances.